Boon or bane?: an investigation into altitude and attitude of youths in Singapore on nature conservation - Tan, Yia Kuan (2015)
Humans are interdependent with nature, yet have inflicted enormous damages to ecosystems and species over centuries of coexistence. The beauty of nature conservation is in its simplicity of a common ideology, as well as its complexity of many possible ways to approach its challenges - from different backgrounds, values, knowledge and understanding. This study was aimed at finding out how might trainee teachers and undergraduates in Singapore, namely in National Institute of Education, National Technological University and National University of Singapore, approach nature conservation issues. Online surveys were conducted to assess readiness in environmental attitude and altitude of 195 undergraduates in 2015. The results revealed that students did understand that all individuals should be responsible for nature’s well-being on Earth, but demonstrated little initiativeness to act upon individual responsibility. Respondents were also generally deficient in environmental knowledge, even undergraduates in Biology and related majors. The study may indicate a need for a change in education in Singapore, where a greater emphasis on developing passion and proactivity in nature conservation should be placed.